Experimental Study of Wave-Induced Response of Piles in Seabed with Various Permeability - Ting Huang; Yinghui Tian; Guoliang Dai; Ao Jiao (Applied Sciences, 2022)
Subjected to continuous wave loading, the responses of pile foundations and seabed develop gradually, severely affecting the serviceability of piled structures. This paper presents the results of a series of flume experiments on pile foundations in fine sandy and silty seabed under regular wave loading. Pile-head displacement and pore water pressure were measured and the effects of pile diameter, cross-section, pile stiffness and wave height were investigated. The experimental results indicate that the pore pressure in fine sandy seabed varied only slightly even under 640 s of wave loading but showed an increase of 15.7–25.9% around a pile. In silty seabed with much lower permeability, pore pressure accumulated quickly due to piles and oscillated impressively at the depth of soil liquefaction. Based on the comparison between the calculated and measured pile-head displacement, we found that the response of smaller-diameter piles in lower-permeability seabed was much more easily magnified by the induced pore pressure. Increasing the pile diameter and attaching fins could lead to a smaller response of piles. Wave height was a major factor in the experiments that affected the development of response.